DEVELOPING MULTIMEDIA-BASED ENGLISH LISTENING MATERIAL FOR ISLAMIC SENIOR HIGH SCHOOL - Yoki Irawan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This study aims at designing and developing multimedia-based English listening material for the first year students of an Islamic Senior High School. The study was a Research and Development (R&D) using ADDIE model. The respondents were 77 students and 4 English teachers of the first-year students of MAN 1 Kerinci. The data of this research were obtained through observation checklist, interviews, questionnaires, validation sheet, and checklist of the product practicality. The findings of product validation and try-out show that the product were interesting and easy to use with minor revisions. Further, it facilitates the students to have self-learning listening. The final product of the study is an executable file (* exe) attached on the CD. The result of the product validation, as well as the try-out, indicates that the material developed is categorized as